Ecosystem response to management of an invasive N2-fixing tree in Hawaiʻi - R.Flint Hughes; Caitlin Morrison; Edward Bufil; James Leary (Trees, Forests and People, 2025)
Many non-native tree species are recognized as problematic to ecosystems they have invaded, and subsequent control efforts have met with varying levels of success. Falcataria falcata is a fast-growing, N-fixing tree that has aggressively invaded landscapes across the Hawaiian Archipelago. Due to their ability to alter Hawaiʻi’s native forest ecosystems, large stature at maturity, and potential for catastrophic tree fall, F. falcata stands pose threats to Hawaiʻi’s native forests, residential communities, and agricultural lands. We investigated responses to chemical control of F. falcata stands immediately after control and during ensuing initial stages of succession. Herbicide treatment of F. falcata stands increased litter inputs of N and P that translated to increased soil nutrient availability. Such increases were exploited by extant understory vegetation consisting of non-native grasses and forbs that formed a continuous layer to severely limit the documented maximum potential germination of nearly 8 million F. falcata seedlings per hectare. Although trajectories of post-control vegetation development were dominated by non-native species in this case, control strategies could be employed to incorporate purposeful plantings of native Hawaiian species, non-native but bio-culturally important species, or desired agricultural species. In the absence of such interventions, however, non-native vegetation dominance following F. falcata control presents a daunting barrier to any hope for native species establishment. Overall, findings indicated that F. falcata control is possible and feasible where understory vegetation is allowed to respond to increased light and nutrient resources and limit potential seedbank recruitment that would otherwise lead to F. falcata stand reestablishment.